KARAKTERISTIK ALAT PENGERING PADI SKALA LAB DENGAN MENGGUNAKAN BAHAN BAKAR SEKAM PADI - Kms. Ridhuan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2011)
The drying process is a stage that is quiteimportant to determine the quality of rice is good, especially the rainy season, so the use ofpaddy dryers (oven) is a must. For the heatsource used fuel waste rice husk obtained fromthe rest of the rice mill. Well as efforts toovercome the energy crisis and environmental sustainability. The purpose of this study is to determine the amount of heat that occurs ineach rack, knowing the rate of decline dryingand knowing the water content of rice and the long drying time. Testing rice dryers done by connecting the oven with a stove burner burningrice husk as a place with a pipe to drain the hotair. In the rice dryer (oven) there is a rack / container of rice be nested six and intersecteach containing 2 kg of rice. Hot airenters from below to above the rack 1 to 6 and then to the outer shelf. From the test results is known that the decrease in average water content of 8.875 %, moisture content of grain /rice after drying that is 16.125 %, the drying rate of 0.2695 % / min, the amount of heat received by rice 173.703 J/ kg. The amount of rice husks are used in a single drying 1 kg with a time of 60 minutes and the rice is dried as much as 12 kgKeywords: drying, oven, rice, husk